Challenges and strategies for successful clinical development of immune checkpoint inhibitors in glioblastoma. (2nd September 2019) - Majd, Nazanin; de Groot, John
ABSTRACT: Introduction : Glioblastoma (GBM) remains an incurable tumor with median overall survival of 15 months with the best standard of care. Immune checkpoint inhibitors (CPI) have been the forefront of immunotherapy advances for treatment of various solid cancers. However, clinical development of CPI in GBM has been challenging due to factors associated with intracranial tumors such as limited space for an inflammatory response, difficulties with repeated sampling, and low tumor mutation burden and immunosuppressive mechanisms unique to GBM. Areas covered : Herein, the authors review the clinical development of CPI in GBM, the challenges involved for their successful implementation, and discuss approaches to overcome these challenges. Expert opinion : Strategies to improve clinical development of CPI in GBM need to carefully address multiple steps that are needed for successful activation and maintenance of tumor-specific immune responses. Multi-modality approaches are needed to achieve this goal and should focus on augmenting tumor T-cell infiltration, activating cytotoxic T-cells, and maintaining their effector function. CPI have been the most successful immunotherapy approach in the treatment of solid cancers and optimization of combinatorial approaches are needed for their successful implementation in GBM.